HUBUNGAN PENGETAHUAN TENTANG PENGGUNAAN ALAT PELINDUNG DIRI (APD) DENGAN KEPATUHAN PENGGUNAAN APD PADA PERAWAT DI PUSKESMAS KUOK - Azzahri, Lira Mufti; Ikhwan, Khairul Ikhwan (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Personal protective equipment (PPE) is a device used by workers for their own safety from potential hazards and work accidents that can be done at work. The impact if not using PPE is a work accident. Based on 2016 World Health Organization data covering 35 million health workers, 3 million were exposed to blood pathogens (2 million were exposed to the hepatitis B virus (HBV), 0.9 million were exposed to the HBC virus and 170,000 were exposed to the HIV / AIDS virus. using personal protective equipment in the work area of the Kuok Health Center in 2018. This type of research is analytic with cross sectional design.The population in this study is the population in this study is a nurse study at the Kuok Health Center involving 49 people needed with total sampling. there is a relationship of knowledge by using PPE with a p value of 0.003. It is expected that respondents will increase knowledge about the use of PPE when working and obediently use